Parental mobile control system for children’s internet use - Md Noor, R.; Syed Jamal, S.N.S.; Zakaria, K.H. (2012)
As children nowadays are getting smarter and more technology wise compared to their own parent, the combination of traditional education method with the technology had help to equip the children with skills regarding to the technology. Even though having all this early exposure towards technology wise is a good idea, however we still need to consider the capability of children at their early stage to able to differentiate between right and wrong. Without a proper guidance and observation, these children might be trapped in between the contentment that technology can possible offer. To prevent more serious cases from happening, an action should been taken. Hence, this paper proposes a parental mobile Control system to monitor their child activities over the Internet. The system contains capturing, detecting and blocking modules that help to prevent the access of adultery sites.